A set-valued framework for coordinated motion control of networked vehicles - J. B. Sousa (2006)
A problem of coordinated control for two networked vehicles is presented, formulated, and solved to illustrate a set-valued framework for the coordinated control of networked vehicles. First, an informal user specification for the coordinated operation of two vehicles is introduced. Second, a formal representation of the objects and relations of interest is presented, and the user requirements are mapped onto a formal specification. Third, the specification is transformed onto a control problem formulation. Finally, the problem is solved using techniques from dynamic optimization and generalizations of the problem are discussed.